Emotions and organizational dynamism - Zerbe, W. J.; Härtel, Charmine E. J., 1959-; Ashkanasy, Neal M., 1945- (Emerald, 2010)
Emotions have widespread effects in organizations and underlie a broad range of dynamics in organizations. This volume explores the role that emotion plays in such diverse organizational phenomena as entrepreneurship, change, service failure, and creativity. The study of emotions in organizations is broadening, with new phenomena being considered through the lens of emotions, and deepening, with theoretical approaches being refined and sharpened. The choice of theme of this volume reflects this tension. Organizations are dynamic, they change and they comprise elements that are constantly moving. They are simultaneously ordered and complicated and complex. Emotions help us understand this dynamism. As the chapters in this volume help us understand and appreciate, emotions are often an underlying energizing and motivating force. Examination of the role of emotions as precursors or mediators of change or innovation or creativity is therefore essential to being able to manage this dynamism.
Description based on print verison record.
Keywords: Organizational behavior -- Psychological aspects.; Work -- Psychological aspects.; Emotions -- Social aspects.; elektronické knihy; electronic books